Fast food nation [videorecording (DVD)] - Linklater, Richard, 1960-; Arquette, Patricia, 1968-; Cannavale, Bobby; Dano, Paul, 1984-; Schlosser, Eric (20th Century Fox Home Entertainment, 2007)
An ensemble drama examining the health issues and social consequences of America's love affair with fast food.